Fracture strength of different veneers on polyetheretherketone (PEEK) frameworks in implant-supported single crowns - Tekin, Samet; Demirci, Fatih; Bakir, Metin (Mosher & Linder, Inc, 2022)
Purpose: To evaluate the fracture strength of polyetheretherketone (PEEK) single crowns veneered with different materials produced by computer-aided design (CAD)-computer-aided manufacture (CAM) after aging. Methods: 60 stainless-steel master dies were prepared with a 1 mm-wide deep chamfer. Sixty PEEK frameworks were produced with a CAD-CAM system for the right maxillary first molar tooth on the dies. PEEK frameworks were divided into six groups (n= 10) according to veneering materials (five CAD-CAM materials and a resin composite). Group ZR: monolithic zirconia (Upcera ST-Color); Group EC: lithium disilicate glass-ceramic (IPS e.max CAD); Group LU: resin nano-ceramic (Lava Ultimate); Group VM: feldspathic ceramic (Vitablocs Mark II); Group VS: zirconia-reinforced lithium silicate glassceramic (VITA Suprinity); and Group CR: indirect resin composite (Gradia). All samples were subjected to a fracture strength test in a universal test device after thermo-mechanical aging and then the results were analyzed statistically using one-way ANOVA and Tukey's post hoc test. In addition, post-fracture analyses of all samples were performed with a stereomicroscope. Results: The differences in fracture strength values of different veneer materials in single crowns with a PEEK framework were statistically significant (P< 0.05). Fracture strength was highest in Group ZR (1665 N), followed by Groups LU (1440 N), EC (1249 N), CR (918 N), VS (754 N), and VM (655 N).
Keywords: Shock Absorption Capacity; Cad/Cam Composite Resin; Fixed Dental Prostheses; in-Vitro Fatigue; Restorative Materials; Surface Modification; Complication Rates; Bond Strength; Performance; Resistance